2023
DOI: 10.17309/tmfv.2023.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Imagery and Agility Training: How do They Affect the Reaction Ability of Futsal Goalkeepers?

Muhammad Fakhrur Rozi,
Riand Resmana,
Iit Selviani
et al.

Abstract: Study purpose. Goalkeepers in futsal require fast movements to anticipate the ball that is heading toward the goal. Therefore, the reaction of the goalkeeper is very necessary to improve the quality in the game. Materials and methods. This research is experimental research conducted using factorial design research using a quantitative approach. In this research, the researchers use treatment with imagery exercises, with audiovisual and visual methods, with measuring the level of ability and agility of each sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…The study's findings revealed a significant improvement in goalkeepers' reaction speed following 10 months of training. This aligns with research by Rozi et al (2023), which emphasizes that agility training can enhance a goalkeeper's reaction speed, a factor influenced by reflexes. A goalkeeper's reaction speed is vital for thwarting opponents' goal attempts, making it essential for goalkeepers to consistently work on enhancing this attribute.…”
Section: Discussionsupporting
confidence: 88%
“…The study's findings revealed a significant improvement in goalkeepers' reaction speed following 10 months of training. This aligns with research by Rozi et al (2023), which emphasizes that agility training can enhance a goalkeeper's reaction speed, a factor influenced by reflexes. A goalkeeper's reaction speed is vital for thwarting opponents' goal attempts, making it essential for goalkeepers to consistently work on enhancing this attribute.…”
Section: Discussionsupporting
confidence: 88%
“…Implementing suitable training methods for practicing soccer playing skills not only enables coaches to make optimal use of available facilities but also eliminates any excuses due to delays or inadequate resources at soccer schools. The choice of an appropriate training method is intricately linked to the training context (Rozi et al, 2023). Factors such as the training environment and the characteristics of the material being practiced should be taken into account when deciding on specific training methods (Mashud et al, 2024;Michailidis, 2022;Wati et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Football in Indonesia is no longer just an ordinary spectacle but has become extraordinary entertainment for football fans in Indonesia. In Indonesia, the sport is most popular with people of all ages (Rozi et al, 2023;Suryadi et al, 2023). Moreover, football, as one of the components of cultural globalization in social life, has become a focal point for social researchers who aim to understand how the outcomes of homogenization and heterogeneity manifest in this phenomenon (Petersen-Wagner, 2017).…”
Section: Introductionmentioning
confidence: 99%